2018
DOI: 10.1158/1078-0432.ccr-17-1623
|View full text |Cite
|
Sign up to set email alerts
|

Foretinib Overcomes Entrectinib Resistance Associated with the NTRK1 G667C Mutation in NTRK1 Fusion–Positive Tumor Cells in a Brain Metastasis Model

Abstract: Purpose: Rearrangement of the neurotrophic tropomyosin receptor kinase 1 (NTRK1) gene, which encodes tyrosine receptor kinase A (TRK-A), occurs in various cancers, including colon cancer. Although entrectinib is effective in the treatment of central nervous system (CNS) metastases that express NTRK1 fusion proteins, acquired resistance inevitably results in recurrence. The CNS is a sanctuary for targeted drugs; however, the mechanism by which CNS metastases become entrectinib-resistant remains elusive and must… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 38 publications
0
19
0
2
Order By: Relevance
“…15 Consistent with these findings, entrectinib was found to prolong survival and delay intracranial progression compared to vehicle in orthotopic CNS xenografts of models that harbour established fusion targets of the drug such as NCI-H228 (NSCLC), 13 BNN2/4 (glioblastoma), 16 and KM12SM (colorectal cancer). 17 In the NCI-H228 model, entrectinib resulted in increased survival compared to crizotinib. These data established preclinical proof-of-principle of the activity of this drug in the CNS.…”
Section: Introductionmentioning
confidence: 99%
“…15 Consistent with these findings, entrectinib was found to prolong survival and delay intracranial progression compared to vehicle in orthotopic CNS xenografts of models that harbour established fusion targets of the drug such as NCI-H228 (NSCLC), 13 BNN2/4 (glioblastoma), 16 and KM12SM (colorectal cancer). 17 In the NCI-H228 model, entrectinib resulted in increased survival compared to crizotinib. These data established preclinical proof-of-principle of the activity of this drug in the CNS.…”
Section: Introductionmentioning
confidence: 99%
“…Note however, that IQ-1 and IQ-3 (both potent JNK inhibitors with an indenoquinoxaline scaffold) did not bind TRK-A [29, 30]. Because TRKA-C are important targets for treatment of several tumors [4042], the parent tryptanthrin and tryptanthrin-6-oxime were evaluated for their binding affinities (K d ) to these 3 kinases. We found that tryptanthrin-6-oxime had higher affinity toward TRKA-C in comparison with the parent alkaloid (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in a brain metastasis model with NTRK1-fusion-positive colon cancer cells, the NTRK1-G667C mutation (which caused moderate resistance), but not the NTRK1-G595R mutation (which induced high resistance), was detected in tumor cells resistant to the TRK inhibitor entrectinib. 35 Therefore, high-dose administration of drugs, which target a driver signal (for instance, an alectinib versus ALK signal) or combined use of standard-dose alectinib and another drug that targets resistance signals (e.g., EGFR TKIs to inhibit an AREG-triggered EGFR signal) may be useful to control resistance in CNS.…”
Section: Discussionmentioning
confidence: 99%